Prolonged extrapyramidal symptoms induced by long‐term, intermittent administration of low‐dose olanzapine along with metoclopramide for emesis: A case report. Issue 3 (18th June 2022) - Sakamoto, Shoko; Deguchi, Yasuhiko; Uchida, Sawako; Itoh, Yoshiaki; Inoue, Koki
Abstract: Background: Antipsychotics with dopamine (D2) receptor antagonism can be effective for emesis in cancer patients. Extrapyramidal symptoms (EPS) induced by typical antipsychotics can be exacerbated by other D2 receptor antagonists. We describe a case of persistent EPS induced by long‐term, intermittent administration of low‐dose olanzapine along with metoclopramide for emesis. Case Presentation: A 59‐year‐old pancreatic cancer patient underwent chemotherapy for 7 months. He was referred to the psychiatry department because of restlessness and insomnia. Although he did not have obvious depressive symptoms, he was anxious about the cancer treatment. For chemotherapy‐induced nausea, he had been prescribed 5 mg of olanzapine intermittently for 7 months. He had last used the drug 9 days before presenting it to us. Additionally, he received metoclopramide and palonosetron as antiemetics. We considered akathisia and cancer‐related anxiety/agitation as possible causes of restlessness and insomnia, and prescribed clonazepam. However, his symptoms worsened, resulting in hospitalization. We reconsidered his symptoms as cancer‐related anxiety/agitation and prescribed quetiapine. Although it was effective, he had tremors and was assessed by a neurologist. Considering the clinical manifestations of rigidity, postural reflex disorder, and a mask‐like face, we suspected drug‐induced parkinsonism and replaced quetiapine with biperiden on the next day, leading to his discharge after 2 weeks. He did not have symptom recurrence even after discontinuation of biperiden. Conclusions: Long‐term, intermittent administration of low‐dose antipsychotics with other antiemetics having D2 receptor antagonism can cause prolonged EPS. Especially in cancer patients, who often require polypharmacy, clinicians should consider exacerbated adverse effects due to drug interactions.